2018
DOI: 10.1080/08897077.2018.1449168
|View full text |Cite
|
Sign up to set email alerts
|

“God Put Weed Here for Us to Smoke”: A Mixed-Methods Study of Religion and Spirituality among Adolescents with Cannabis use Disorders

Abstract: Together, findings suggest that for adolescents with SUDs, religion and spirituality may not counteract the use of cannabis, which may be explained by adolescents' views of their substance use as being consistent with their spirituality and under their control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 62 publications
0
6
0
2
Order By: Relevance
“…Some of the studies with neutral or negative findings include those with mixed results. For instance, a study by Yeterian et al (2018) found that among adolescents being seen in an outpatient SUD program, higher baseline spirituality predicted a lower likelihood of heavy drinking at follow-up, even more so than religiosity. However, higher levels of religion and spirituality at the baseline were related to increased marijuana use at the 6-month follow-up, as participants reported that they felt more spiritually connected when they were high on marijuana.…”
Section: Sections Of the Studymentioning
confidence: 99%
“…Some of the studies with neutral or negative findings include those with mixed results. For instance, a study by Yeterian et al (2018) found that among adolescents being seen in an outpatient SUD program, higher baseline spirituality predicted a lower likelihood of heavy drinking at follow-up, even more so than religiosity. However, higher levels of religion and spirituality at the baseline were related to increased marijuana use at the 6-month follow-up, as participants reported that they felt more spiritually connected when they were high on marijuana.…”
Section: Sections Of the Studymentioning
confidence: 99%
“…This is in line with the observation that some individuals feel more spiritual when under the influence of cannabis. 81 Cannabis is also considered a risk factor for developing psychosis. 82 …”
Section: Discussionmentioning
confidence: 99%
“…11,19 There are even reports that have shown that some kinds of spirituality were not inhibitors but facilitators of marijuana consumption. 19,20,21 The aim of this research is to test the impact of being a member of a religious community on the use of tobacco and cannabis by adolescents. We used a sample of 1935 teenagers of Tarragona (Spain).…”
Section: Introductionmentioning
confidence: 99%